Сlinical, functional and morphological results of diabetic macular edema antiangiogenic treatment in patients with diabetes mellitus type two - L. K. Moshetova; I. V. Vorobieva; E. V. Parfenova; D. A. Merkushenkova; P. I. Makarevich; V. I. Alekhnovich (Oftalʹmologiâ, 2014)
Purpose: To evaluate of retinal morphology and function progress in patients with diabetes type 2 and DME consistent with the level of pathogenetic factor in tear fluid.Methods: The progress of visual acuity, retinal thickness and photosensitivity after ranibizumab intravitreal injection has been assessed.Results: Statistically significant increase in visual acuity, retinal photosensitivity, decrease of retinal thickness and VEGF A level was found in the tear fluid after injection. The correlation of VEGF level in tear fluid with visual acuity after procedure was found to be negative. Conclusion: Ranibizumab intravitreal injection is a pathogenic treatment leading to morphological and functional retinal state improvement.